A Low-Profile Broadband Array Antenna for Home Repeater Applications - Sung Joon Yoon; Jaehoon Choi (Journal of the Korean Institute of Electromagnetic Engineering and Science, 2018)
This paper reports on the proposed design of a low profile broadband array antenna for home repeater applications. The proposed antenna consists of 1 × 4 patch elements and two ground planes, one of which is slitted. By using the gap feeding method, the impedance matching of the antenna is improved by a multi-resonance phenomenon. The proposed antenna provides a wide −10 dB reflection coefficient bandwidth simultaneously covering the Global System for Mobile communications (GSM-1800), Personal Communications Service (PCS), and the Universal Mobile Telecommunication System (UMTS) bands (1.67–2.32 GHz). In order to reduce the mutual coupling between adjacent patch elements, slits are embedded in the ground plane. An isolation level of −20 dB is realized over the entire operating frequency band.